PENGARUH PROGRAM SENAM KEBUGARAN TERSTRUKTUR TERHADAP FISIOLOGIS KEBUGARAN FISIK PADA DEWASA MUDA - Lilik Pranata; M.K. Fitriani Fruitasar; Novita Anggraini; Masayu Azizah; Nilda Lely (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2026)
Introduction: Structured fitness exercises are an effective strategy for improving the physical health of young adults. A systematic approach to exercise can optimise physiological function and support an active and healthy lifestyle. Objective: to determine the effect of fitness exercises on the physiological fitness of young adults. Method: A quasi-experimental design with a pre-test and post-test group approach, conducted at a fitness centre in Palembang City, from 1 to 31 July 2025, over 4 weeks (3 times a week), consisting of preparation, participant recruitment, intervention, and post-intervention measurement stages. The sample size was 40 individuals, measuring fitness levels before and after the intervention. weeks (3 times per week), consisting of preparation, participant recruitment, intervention, and post-intervention measurement. The sample size was 40 individuals, with fitness measured using the Step Test (Harvard Step Test). Participants performed 30 repetitions of step-ups per minute for 3 minutes. Heart rate is measured at the 60th second after the test is completed. The intervention group follows an exercise programme for 4 weeks, with a frequency of 3 times per week, a duration of 45–60 minutes per session, and moderate intensity (60–75% HRmax). The structured fitness exercise programme includes Warm-up, Core Exercises, Cool-down. The instructor led the sessions to ensure movements adhered to safety standards. Results: significant improvement in physical fitness (Z = -5.518; P = 0.000). Since p 0.05, it can be interpreted that there was a significant difference in physical fitness between before and after the intervention. Discussion: The research results show that the structured fitness exercise programme has a significant effect on improving the physiological fitness of young adults. The improvement in fitness categories from the pre-test to post-test phase reflects physiological adaptations consistent with the literature on the effects of aerobic exercise and rhythm-based exercise on physical capacity.